Effects of oxygen non-stoichiometry on the physical properties of the YBaCo2 O5 + δ layered cobaltites - Aurelio, Gabriela (2006)
We have synthesized the layered cobaltites YBaCo2 O5 + δ with different oxygen contents (δ1 and δ2), and characterized its structural and physical properties using various experimental techniques within the 80-500 K temperature range. Two superstructures have been identified due to the ordering of oxygen vacancies. One of them (corresponding to δ ≃ 0.50) shows a metal-insulator transition at room temperature, while both exhibit a sequence of magnetic transitions AFM-FM-PM as the temperature is increased. We have determined the second-order nature of the FM-PM magnetic transition using the Banerjee criterion. We also show that there exist intrinsic differences between both samples in terms of the charge carriers involved, which manifest in the transport properties.